Criticism of Eugene O’Neill’s Works: Exploring the Criticism and Biographies of Eugene O’Neill’s Works (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Being a prominent literary figure, Eugene O’Neill won friends as well as critics through his plays. Scholarship and criticism on O’Neill’s works is vast and varied. His works are analyzed from various points of views by renowned scholars not only in America but in the parts of the world, including India. It is worthwhile to have a study of the present criticism on O’Neill. The scope of present study will also become evident from the study of the existing criticism on O’Neill. The existing criticism on O’Neill consists of biographies, critical books, collections of critical essays and articles. The first biography of O’Neill is Barrett H. Clark’s Eugene O’Neill (New York McBride, 1926). This was revised and reissued in 1929 as Eugene O’Neill The Man and His Plays. This is a pioneer work, and it covers O’Neill’s life and career up to the production of The Fountain. It has scanty information, but interesting, chiefly because of the biographical information which O’Neill himself imparted to Clark.